MURAD MUHAMMAD DOST’S STORIES OF SPIRITUALITY - JABBOROVA DILAFRUZ (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
a new spirit, a new ideological-aesthetic direction began to appear in the stories created in the 80s - the purpose was to show the process of formation of the sense of national identity in the spiritual world and psyche of the hero, which Murad We tried to show through the analysis of the story "Mustafa" by Muhammad Dost. The characters he created harmoniously embody beauty and tragedy, a process that has not yet been fully described in our literature. In this sense, the main focus of the article is the aspiration of Elomonov, Gaybarov, and Mustafa, the heroes of Murad Muhammad Dost’s story.